Loneliness in Bereaved Children and Adolescents - Vanessa Budiawan Soetioso; Izzatul Fithriyah (Jurnal Psikiatri Surabaya, 2024)
Introduction: Bereavement in children and adolescents was a common life event, but often unrecognized. It is potentially followed by a reaction of grief. Bereavement may cause feelings of loneliness, which is associated with poor mental well-being. This study aims to understand the impact of loneliness on bereaved children and adolescents. Methods: Literature Review. Results: Childhood loss is a significant social and public health problem associated with developmental disorders — including relational, academic, and occupational functioning — as well as an increased risk of mental health problems. Loneliness occurs in childhood and adolescence is a risk factor for poorer well-being. Loneliness in children and adolescents is a risk factor for depression, social anxiety, behavioral disorders, hyperactivity, substance abuse, suicide, and premature death. Studies showed more than 50% of mental health problems develop during childhood and adolescence, with the average age being 14.5, and poorer well-being resulting from loneliness has a long-term impact on health and well-being during adulthood. Conclusions: Bereavement during childhood and adolescence period is a risk of loneliness, which is associated with a variety of mental and behavioral health problems, decreased academic performance, and impairments in developmental tasks. Early prevention and intervention are needed to reduce the risk of disorders later in life and to increase resilience among bereaved children and adolescents. Keywords: Bereavement, Loneliness, Well-Being, Children And Adolescent